The Post-Phenomenology of Place: Moving Forward from Phenomenological to Post-Structural Readings of Place. Issue 2 (1st June 2018) - Talebian, Nima; Uraz, Turkan Ulusu
Abstract : This study aims to explore the concepts of 'place' and 'place-experience' within the context of Post-phenomenology. During 70's, humanistic geographers have introduced 'phenomenology of place' as a revolutionary approach toward place, which has been largely condemned by Marxist, Feminist and Post-Structural critiques through the last three decades. Accordingly, this study attempts to merge these place-related critiques in order to clarify a new framework titled 'Post-phenomenology of place'. 'Post-phenomenology', as a novel philosophical trend, is a merged school of thought, trying to re-read phenomenology based on Post-structuralism, Pragmatism and Materialism. In this study after a theoretical review on the formation of Post-phenomenology, the various aspects of place are discussed in order to clarify distinctions and paradoxes between phenomenological and Post-phenomenological understandings of place.